Springer Images.
Springer Images is a growing collection of scientific images that spans the scientific, technical and medical fields, including high-quality clinical images from images.MD. The continually updated collection – currently over 5 million images – gathers photos, graphs, histograms, figures, and tables, and is available to libraries and their patrons via a searchable online database. The SpringerImages interface enables users to search faster, more broadly and more accurately, through captions, keywords, context and more, even jumping from the image to the source article. Users can create personalized image “sets,” and can easily export images for use in their own presentations or lectures.
Keywords: Beelddatabank